N-type compensated silicon: resistivity, crystal growth, carrier lifetime, and relevant application for HIT solar cells. (24th April 2017) - Li, Shuai; Gao, Wenxiu; Li, Zhen; Cheng, Haoran; Lin, Jinxia; Cheng, Qijin
Abstract: N-type compensated silicon shows unusual distribution of resistivity as crystal grows compared to the n-type uncompensated silicon. In this paper, evolutions of resistivities with varied concentrations of boron and varied starting resistivities of the n-type silicon are intensively calculated. Moreover, reduction of carrier mobility is taken into account by Schindler's modified model of carrier mobility for the calculation of resistivity of the compensated silicon. As for substrates of solar cells, optimized starting resistivity and corresponding concentration of boron are suggested for better uniformity of resistivity and higher yield (fraction with ρ > 0.5     Ω ⋅ cm ) of the n-type compensated Cz crystal rod. A two-step growth method is investigated to obtain better uniformity of resistivity of crystal rod, and this method is very practical especially for the n-type compensated silicon. Regarding the carrier lifetime, the recombination by shallow energy-level dopants is taken into account for the compensated silicon, and evolution of carrier lifetime is simulated by considering all main recombination centers which agrees well with our measured carrier lifetimes as crystal grows. The n-type compensated silicon shows a larger reduction of carrier lifetime compared to the uncompensated silicon at the beginning of crystal growth, and recombination with a oxygen-related deep defect is sufficient to describe the reduction of degraded lifetime. Finally, standard heterojunction with intrinsic thin-layer (HIT) solar cells are made with substrates from the n-type compensated silicon rod, and a high efficiency of 22.1% is obtained with a high concentration ( 0.8 × 10 16   cm − 3 ) of boron in the n-type compensated silicon feedstock. However, experimental efficiencies of HIT solar cells based on the n-type compensated silicon show an average reduction of 4% along with the crystal length compared to the uncompensated silicon. The obtained results enrich our knowledge on the n-type compensated silicon and contribute to the development of n-type compensated silicon-based solar cells for commercial application.